Magnetic Resonance-Guided Cancer Therapy Radiomics and Machine Learning Models for Response Prediction - Jesutofunmi Ayo Fajemisin; Glebys Gonzalez; Stephen A. Rosenberg; Ghanim Ullah; Gage Redler; Kujtim Latifi; Eduardo G. Moros; Issam El Naqa (Tomography)
Magnetic resonance imaging (MRI) is known for its accurate soft tissue delineation of tumors and normal tissues. This development has significantly impacted the imaging and treatment of cancers. Radiomics is the process of extracting high-dimensional features from medical images. Several studies have shown that these extracted features may be used to build machine-learning models for the prediction of treatment outcomes of cancer patients. Various feature selection techniques and machine models interrogate the relevant radiomics features for predicting cancer treatment outcomes. This study aims to provide an overview of MRI radiomics features used in predicting clinical treatment outcomes with machine learning techniques. The review includes examples from different disease sites. It will also discuss the impact of magnetic field strength, sample size, and other characteristics on outcome prediction performance.